Histological and immunohistochemical study of luteinizing hormone producing cells in the adenohypophysis cerebri of buffalo - KHAN, MASSARAT; SAIGAL, R P; SETHI, R S (The Indian Journal of Animal Sciences, 2014)
The hypophysis cerebri of 56 buffalo of either sex, of different age groups and in different phases of reproduction cycle were used for the study. The paraffin sections of 5 um thickness were stained with differential staining and immunoilistochemical techniqucs. The luteinizing hormone-producing (LH) cells were round, oval and stellate shaped with processes. The estimated average diameter of cells was 8.2Â±0.16 um with insignificant regional differences. Group- wise the Lll cells diameter was minimum (5.6um) in t-week-old male calf and maximum (8.0um) in adult males. In females. the cell diameter varied from 8.6 um (during follicular phase) to 10 8 um (in pregnancy over 3 months).